Integration of custom street view and low-cost motion sensors - Bakirman, Tolga; Gumusay, Mustafa Umit (SELCUK UNIV PRESS, 2020)
Virtual reality is an artificial computer-generated environment generally referred as virtual reality environment which can be navigated and interacted with by a user. Street View, which was released by Google in 2007, is an ideal tool to discover places and locations. This service doesn't only provide spatial information, but also a virtual reality environment for the user. Since this service is only available in certain locations, Google enables users to create a street view with custom panoramic images with the help of Google Maps Application Programming Interface (API) for JavaScript. In this study, it is aimed to integrate body motions with a custom created street view service for Yildiz Technical University Davutpasa Campus which has a historical environment and huge places to discover. Microsoft Kinect for Xbox 360 motion sensor along with Flexible Action and Articulated Skeleton Toolkit (FAAST) interface has been employed for this purpose. This integration provides a low-cost alternative for virtual reality experience. The proposed system can be implemented for virtual museums, heritage sites or planetariums consisting of panoramic images.
Keywords: Street view; Kinect; Virtual reality; Body motion control; Panorama; VIRTUAL-REALITY; Engineering